Effect of Modes of Video Presentation of Metacognitive Strategies on Secondary School Students’ Achievement in Reading Comprehension in North Central Nigeria - Ijiga, Pius Adakole (Journal of Education and Vocational Research, 2014)
Many senior secondary school students struggle with reading comprehension of expository texts in Nigeria, leading to mass failure in the Senior School Certificate Examinations conducted by the West African Examination Council (WAEC). Research on improving reading comprehension has dwelt on isolated reading strategies taught the learners through the conventional lecture method. No study has explored the effect of video-based training on metacognitive strategies and verbal ability on students’ achievement in reading comprehension. This study, therefore investigated the effect on achievement in reading comprehension of three modes of video instruction in metacognitive strategies of senior secondary school students in North Central zone of Nigeria. It also examined the main and interaction effects of verbal ability level, gender and treatments on achievement in reading comprehension. The study used a quasi-experimental post-test only equivalent group design. Three secondary schools were selected from three States in the North Central geo-political zones in Benue, Nasarawa and Kogi States. In each of the three schools, a total of 120 senior secondary school (SS II) students of both sexes were randomly sampled and assigned to three experimental groups and a control group. The study was guided by five hypotheses which were tested at p<0.05 significant level. A Reading Comprehension Achievement Test (RCAT), developed by the researcher and validated by experts, was the main instrument used for data collection. The data collected were analyzed using t-test and Analysis of Variance (ANOVA). The research findings indicated significant effect of Drill and Practice Video Instructional Mode (DPVIM), Interactive Video Instructional Mode (IVIM), and main and interaction effects of verbal ability level and treatments. No significant effects on achievement in reading comprehension were found for Tutorial Video Instructional Mode (TVIM) and main and interaction effects of gender and treatments. Based on these findings, it is recommended that reading comprehension teachers should make use of video instruction in developing comprehension skills of secondary school students in Nigeria.